Anti Lithiasis Activity of Avocado (Persea americana Mill) Leaves Extract in White Male Rats - IETJE WIENTARSIH; RINI MADYASTUTI; BAYU FEBRAM PRASETYO; ANGGARA ALDOBRATA (Bogor Agricultural University, Indonesia, 2012)
In Indonesia, avocado leaves have been used as traditional medicines for diureticum to cure urolithiasis. This research was to determine anti lithiasis activity of avocado leaves (Persea americana Mill) extract on white male rats nefrolithiasis model induced by ethylene glycol. Ethanol extraction method was used to get extract of avogadro leaves. Twenty adult male white rats were divided into 4 different induction treatments i.e. aquadest, ethylene glycol 0.75% and ammonium chloride 2%, and extract of avocado leaves with different levels of 100 and 300 mg/kg bw respectively. Their body weight was measured daily to determine their growth ratio. And at the end of the trial, the kidney was analyzed its calcium level and inhibitory activity to formation of calcium oxalate crystals. The results showed that the amount of calcium level in the kidney of rats treated with extract of avogadro leaves was significantly decreased than that of rats treated with ethylene glycol 0.75% and ammonium chloride 2% (P < 0.05). The extract avocado leaves as a herbal remedy can be recommended as a phytotherapeutic agent especially for preventive action for urolithiasis diseases.